Role of the epithelial barrier in intestinal fibrosis associated with inflammatory bowel disease: relevance of the epithelial-to mesenchymal transition - Macias-Ceja, Dulce C.; Mendoza-Ballesteros, M. Teresa; Ortega-Albiach, María; Barrachina, M. Dolores; Ortiz-Masià, Dolores (Frontiers in Cell and Developmental Biology, 2023)
In inflammatory bowel disease (IBD), chronic inflammation in the gastrointestinal tract can lead to tissue damage and remodelling, which can ultimately result in fibrosis. Prolonged injury and inflammation can trigger the activation of fibroblasts and extracellular matrix (ECM) components. As fibrosis progresses, the tissue becomes increasingly stiff and less functional, which can lead to complications such as intestinal strictures, obstructive symptoms, and eventually, organ dysfunction. Epithelial cells play a key role in fibrosis, as they secrete cytokines and growth factors that promote fibroblast activation and ECM deposition. Additionally, epithelial cells can undergo a process called epithelial-mesenchymal transition, in which they acquire a more mesenchymal-like phenotype and contribute directly to fibroblast activation and ECM deposition. Overall, the interactions between epithelial cells, immune cells, and fibroblasts play a critical role in the development and progression of fibrosis in IBD. Understanding these complex interactions may provide new targets for therapeutic interventions to prevent or treat fibrosis in IBD. In this review, we have collected and discussed the recent literature highlighting the contribution of epithelial cells to the pathogenesis of the fibrotic complications of IBD, including evidence of EMT, the epigenetic control of the EMT, the potential influence of the intestinal microbiome in EMT, and the possible therapeutic strategies to target EMT., Ffinally we discuss the pro-fibrotic interactions epithelial-immune cells and epithelial-fibroblasts cells.